Pengaruh Inflasi Dan Tingkat Ketenagakerjaan Terhadap Produk Domestik Regional Bruto Di Negara-Negara Apec: Analisis Regresi Data Panel Tahun 2010–2019 - Maulana, Ilham; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of inflation and unemployment rates on Gross Regional Domestic Product (GRDP) in APEC member countries from 2010 to 2019. By utilizing the panel data regression method, this study integrates dimensions between countries and time to capture economic dynamics in more depth. The information obtained comes from official publications from international institutions and covers 21 APEC member countries. The resulting regression models include the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), where the selection of the most optimal model is determined through the Chow test, Hausman test, and Lagrange Multiplier test. The analysis shows that inflation has a negative and significant impact on GRDP, while the labor absorption rate has a positive and significant impact. These results indicate that price stability and labor acceptance are key elements in driving economic growth in the APEC region. This study is expected to be a reference for economic decision makers in formulating more efficient and comprehensive macroeconomic strategies.